Selection model of representative items for the subcontractors’ cost index in multi‐family housing projects - Park, Sung-Chul; Hong, TaeHoon; Koo, Kyo-Jin; Hyun, Chang-Taek (Journal of Civil Engineering and Management, 2010)
Price index has played an important role in measuring the past performance of an industry, which it does by tracking the cost of the items used in the industry. It is the most widely used industry performance indicator because a small number of representative items covers a wide range of costs. The construction industry consists of various facility types that can be organized into many subcontractors’ works. Unfortunately, the existing cost indexes have difficulty monitoring the fluctuation of the subcontractors’ costs since they select representative items in macro‐scale terms, such as the type of construction or facility. Therefore, this study was conducted to develop a selection model that can select the effective representative items included in the subcontractors’ costs. To determine the characteristics of the subcontractors’ costs, the curve estimation function of SPSS® 12.0 for Windows was applied to the priced bills of quantities of 30 multi‐family housing projects. The results of the analysis show that the relationship between the coverage ratio and the percentage of the number of representative items follows Pareto’s principle. Based on this, a selection model of representative items was developed, using the tangent function. The case study that was conducted to verify the usability of the model revealed that the proposed model can efficiently select the effective representative items from the cost items of each subcontractor’s work included in multi‐family housing projects. First Published Online: 24 Jun 2011